2011
DOI: 10.1080/00207594.2011.590494
|View full text |Cite
|
Sign up to set email alerts
|

The effects of functional group counseling on inspiring low‐achieving students’ self‐worth and self‐efficacy in Taiwan

Abstract: In this study, we investigated the effects of functional group counseling on inspiring low achievers' self-worth and self-efficacy in Taiwan. Forty-three 10th grade low-achieving students volunteered as the Experimental Group to join a 24-week intervention, which integrated and utilized functional group counseling; another 51 10th grade low-achieving students volunteered to be Comparison Group I. In addition, 43 10th grade moderate or high academic achieving students volunteered to be Comparison Group II. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…This interpretation fits well with the Taiwanese educational system which emphasizes high achievement at the expense of promoting individual interest and motivation. Under the pressure of highly competitive college entrance exams and Taiwanese traditional perspectives toward children, most high school students are encouraged or expected to perform well academically (Hong et al, 2011) with little attention paid to student interest and enjoyment in learning. Unfortunately, this practice may ultimately lead to lowering public understanding of science.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation fits well with the Taiwanese educational system which emphasizes high achievement at the expense of promoting individual interest and motivation. Under the pressure of highly competitive college entrance exams and Taiwanese traditional perspectives toward children, most high school students are encouraged or expected to perform well academically (Hong et al, 2011) with little attention paid to student interest and enjoyment in learning. Unfortunately, this practice may ultimately lead to lowering public understanding of science.…”
Section: Discussionmentioning
confidence: 99%
“…The PISA framework and datasets provide a wide variety of variables related to the scientific literacy performance of students. Research studies have indicated that science‐related interest, enjoyment, engagement, and self‐efficacy (Hong, Lin, Wang, Chen, & Yu, ; Jack et al, ), as well as epistemic agency (Miller, Manz, Russ, Stroupe, & Berland, ) and inquiry‐based science teaching and learning (Brown, ), have significant impacts on students' scientific literacy performance. In addition to scientific literacy, student resilience has become a favorite topic for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In their attempt to characterise reading processes and text comprehension of readers of diverging proficiency, Alexander and Murphy (1998) distinguished the following reader profiles: highly competent, seriously challenged, resistant, effortful and nonstrategic. From the findings, it can be concluded that readers in this study with the best and average task performance had some characteristics of effortful processors.…”
Section: Discussionmentioning
confidence: 99%
“…Differences concerning self-regulation in task-oriented reading among low-achieving adolescents have been proposed in the literature (Alexander & Murphy, 1998;Biancarosa & Snow, 2006), but it is not clear what differences can be empirically found and to what degree they are relevant for task achievement. Although such differences have been demonstrated between readers of lower and higher proficiency (Vidal-Abarca et al, 2010), it is useful to know whether differences in task achievement within the group of low-achieving adolescent readers are related to differences in regulation.…”
Section: Present Studymentioning
confidence: 99%